The answer is 3 over 7. First you have to set up the equation like how you just did. Then you multiply numerator to numerator and denom. to denom. and you get 12 over 28 which reduces to 3 over 7 when you divide the numerator and denomerator by 4.
x = 7 7-4/3 x 7 = 1/7 3/21 = 1/7
7/8 / 3/4= 7/8 x 4/3== 7/6
3/4 x 7/12 is 7/16
7 x 3/4 = 21/4
okay if x-4=3 then x=7 bcause 4+3=x = 4+3=7 and 7-4=3!
3/7 x -1/4 = -3/28
4/7 x 3/4 is 3/7
4/7 x 3/3 = 4x3/7x3 = 4/7 Alternatively, you may realise that 3/3 = 3 ÷ 3 = 1 → 4/7 x 3/3 = 4/7 x 1 = 4/7
x = 7 7-4/3 x 7 = 1/7 3/21 = 1/7
7/8 / 3/4= 7/8 x 4/3== 7/6
3/4 x 7/12 is 7/16
7/16 x 4/3 x 1/2 = 7/24
7 x 3/4 = 21/4
7/16 x 4/3 x 1/2=7/16 x 4/6=[ 28/96 ]=[7/24] (reduced)
To solve for x, you will need to set the two expressions equal to each other: (x - 3)/4 = (x + 3)/7. Cross multiply to get 7(x - 3) = 4(x + 3). Expand and solve for x to get 7x - 21 = 4x + 12. Simplify to get 3x = 33, and then divide by 3 to find x = 11. So, x equals 11.
x+3/4 = 7/8 Is the same as: x+6/8 = 7/8 x = 7/8- 6/8 x = 1/8
-3/5 x 4/7 is -12/35